Hot corrosion behavior of (Gd0.9Sc0.1)2Zr2O7 in V2O5 molten salt at 700–1000 °C. Issue 12 (15th August 2017) - Zhang, Chenglong; Li, Mingzhu; Zhang, Yuchen; Guo, Lei; Dong, Junxiu; Ye, Fuxing; Li, Linwei; Ji, Vincent
Abstract: Hot corrosion behavior of (Gd0.9 Sc0.1 )2 Zr2 O7 ceramic exposed to V2 O5 molten salt at 700–1000 °C was investigated, providing better understanding of its corrosion resistance as a promising thermal barrier coating. Obvious corrosion reaction occurred between (Gd0.9 Sc0.1 )2 Zr2 O7 and V2 O5 molten salt after 4 h heat treatment, corrosion products being temperature dependent. At 700 °C, large amount of Sc2 O3 doped ZrV2 O7 and GdVO4, together with a minor amount of Sc2 O3 -stabilized tetragonal ZrO2 ( t -ZrO2 ), formed on the sample surfaces. With the increase of the test temperature, Sc2 O3 doped ZrV2 O7 turned to decompose, leading to the formation of more t -ZrO2 . At 900 °C and 1000 °C, the corrosion products were composed of GdVO4 and t -ZrO2 . The mechanism by which the corrosion reaction occurs is proposed based on phase diagrams and Lewis acid-base rule.